An overview on water masses in the China seas - Zhu, Jia; Hu, Jianyu; Zheng, Quanan (Frontiers in Marine Science, 2022)
This paper overviews progress in the research of water mass classification in the China seas, consisting of the Bohai Sea, the Yellow Sea, the East China Sea, the Taiwan Strait and the South China Sea. So far, oceanographers have achieved systematic research results in terms of the concept and definition, theory and method, characteristics and variation of water masses in the China seas. Here 3-D visualized diagrams are developed to illustrate spatial distributions of classified water masses in the China seas. Meanwhile, core values or ranges of temperature and salinity for individual water mass are integrated. Seasonal variations and formation mechanisms of water masses are briefly analyzed.